Pedro Kipte and the Pulahanes in Masbate, 1898-1902 - Pelorina, Renato Noynay
The writing of Masbate's history particularly during the revolutionary period is long overdue. Masbate is not well represented in local history written by both Bicol and Visayan local historians. This dissertation is on Pedro Kipte and the Pulahanes in Masbate during the revolutionary period with particular focus from 1898 to 1902. Like the Katipuneros, the Pulahanes in Masbate have their share in the collective Filipino people's struggle for freedom from colonialism. The dissertation specifically examines, first, how geography played a significant role in the birth and development of Pulahan movement in masbate. Second, how the Pulahanes viewed and responded to the Tagalog revolutionary forces from Luzon who organized the revolutionary government in the island. Third, how the Pulahanes viewed, fought and resisted the American expeditionary forces when the latter arrived from Luzon to occupy Masbate. This study uses the historical method. It is primarily based on archival materilas, published memoirs and oral intwerviews. Field works was conducted in the different places in Masbate especially those towns and barrios where the descendants of Pedro Kipte are still living at present. Field work interview was conducted for about two months from November to December 2009. This study concludes that the Pulahanes emerged in Masbate because of the exploitative political and economic conditions under the Spanish colonial government. Under the leadership of the legendary and largely forgotten Visayan fighter Pedro Kipte, the Pulahanes had their own initiative in fighting against colonialism and successfully ended Spanish colonialism in Masbate. The Pulahanes are the true liberators of Masbateños from foreign yoke. This being so, they should be considered heroes during the revolutionary period in Masbate.